Nizamiyah And Bologna: A Comparative Study Of The Curriculum Historiography Of Two Higher Education Civilizations In The World - Nuraini Mannan; Zulkarnaini; Nurjannah Ismail; Subhan; Mujiburrahman (International journal of technology and education research, 2026)
Studies This motivated by fundamental problems in discourse education global height, namely gap understanding to root historical formation difference paradigmatic between tradition Islamic and Western education. The Nizamiyah Madrasah and the University of Bologna, both of which born in the 11th century, represents two educational models height that forms face Sunni Islamic civilization and Latin Europe, but studies that examine both of them in a way comparative in perspective historiography curriculum still very rare. Research This aim For analyze in a way deep comparison foundation epistemological, structure curriculum, methods learning, as well as impact sociocultural and political from second institutions those. Types research used is studies literature with approach qualitative-comparative. Research results disclose four findings main. First, in epistemological, Nizamiyah based on orientation theocentric which places revelation as source truth absolute and rational as tool aid, while Bologna relies on orientation anthropocentric-scriptural which places ratio and dialectics as center methodology. Second, the structure curriculum Nizamiyah nature fiqh-centric which leads to integration knowledge in religious framework, while Bologna is centralized jurisprudence leading to specialization profession secular. Third, the method learning Nizamiyah emphasize authority sanad and transmission knowledge through halaqah, while Bologna developed a culture of disputation that encourages criticism and innovation. Fourth, second curriculum functioning as instrument legitimacy politics and formation identity each civilization. Research conclude that fundamental differences between second institutions No lies in the aspect technical curriculum, but rather on the answers philosophical on question about essence science and purpose education. Implementation findings This offers a synthesis model curriculum education contemporary Islamic high school that integrates spiritual power of Nizamiyah with sharpness Bologna analytical.